فعالية برنامج تدريبي قائم على نظرية التعلم الخبراتي في الاندماج الأكاديمي والرشاقة المعرفية لدى طالبات جامعة للأزهر - البديوي، عفاف سعيد فرج (الجمعية المصرية للدراسات النفسية, 2021)
هدف البحث إلى التعرف على فعالية برنامج تدريبي قائم على نظرية التعلم الخبراتي في الاندماج الأكاديمي والرشاقة المعرفية لدى طالبات كلية الدراسات الإنسانية بتفهنا الأشراف بالدقهلية جامعة الأزهر، وتكونت العينة من (٦٢) طالبة تم تقسيمهن إلى مجموعتين إحداهما تجريبية والأخرى ضابطة، وأعدت الباحثة مقياسي الاندماج الأكاديمي والرشاقة المعرفية ومقياس فعالية المعالجة التجريبية والجلسات التدريبية القائمة على التعلم الخبراتي، وتوصلت النتائج إلى وجود فروق دالة إحصائيا عند مستوى (0.01) بين متوسطي درجات طالبات كل من المجموعتين التجريبية والضابطة في القياس البعدي على مقياس الاندماج الأكاديمي لصالح المجموعة التجريبية، ووجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطات درجات كل من القياس القبلي والبعدي والتتبعي للمجموعة التجريبية في الاندماج الأكاديمي (الأبعاد والدرجة الكلية)، حيث كانت الفروق بين القياسين القبلي والبعدي لصالح البعدي، وبين القبلي والتتبعي لصالح التتبيعي، بينما لم تظهر فروق بين القياسين البعدي والتتبعي، كما توصلت النتائج إلى وجود فروق دالة إحصائيا عند مستوى (0.01) بين متوسطي درجات طالبات كل من المجموعتين التجريبية والضابطة في القياس البعدي على مقياس الرشاقة المعرفية لصالح المجموعة التجريبية، ووجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين متوسطات درجات كل من القياس القبلي والبعدي والتتبعي للمجموعة التجريبية في الرشاقة المعرفية (الأبعاد والدرجة الكلية)، حيث كانت الفروق بين القياسين القبلي والبعدي لصالح البعدي، وبين القبلي والتتبعي لصالح التتبعي، بينما لم تظهر فروق بين القياسين البعدي والتتبعي.
The aim of the research is to identify the effectiveness of a training program based on the theory of experiential learning in developing academic engagement and cognitive agility among students of the College of Human Studies in Tafahna Al-Ashraf in Dakahlia Al-Azhar University, and the sample consisted of (62) students who were divided into two groups, one experimental and the other controlling, and the researcher prepared a scale of academic engagement, cognitive agility and the measure of the effectiveness of experimental treatment and training sessions based on experiential learning, The results concluded that there are statistically significant differences at the level of (0.01) between the mean scores of the students of each of the experimental and control groups in the post-measurement on the scale of academic engagement in favor of the experimental group, and the existence of statistically significant differences at the level of (0.01) between the mean scores of each From the pre, post and tracer measurement of the experimental group in the academic engagement (dimensions and the total score),Where the differences between the two measurements, the tribal and the posterior, were in favor of the postal, and between the tribal and the tracer, in favor of the Tabi'i, while there were no differences between the two measurements, the posterior and the posterior, the existence of statistically significant differences at the level of (0.01) between the mean scores of the students of each of the experimental and control groups in the post measurement on the scale of cognitive agility in favor of the experimental group, and the existence of related differences Statistical significance at the level of (0.01) between the mean scores of each of the pre, post and tracer measurements of the experimental group in cognitive agility (dimensions and total score), Where the differences between the two measurements, the tribal and the posterior, were in favor of the postal, and between the tribal and the tracer, in favor of the Tabi'i, while there were no differences between the two measurements, the posterior and the posterior.
Keywords: علم النفس التربوي -- نظريات التعلم -- نظرية التعلم الخبراتي -- الاندماج الأكاديمي